Hybrid Creatures: Mrs Patrick Campbell's Contributions to Pygmalion. Issue 1 (May 2016) - Gregory, Fiona
This paper considers the role of actress Stella (Mrs Patrick) Campbell in the creation and reception of George Bernard Shaw's play Pygmalion, which premiered its first English-language production at His Majesty's Theatre in April 1914. Accounts of Pygmalion often perpetuate a narrative that presents Campbell as an egocentric performer who systematically dismantled Shaw's vision for the play and forced him to exert greater authorial control over its later incarnations. This paper reassesses Campbell's creative contribution to Pygmalion and the influence she had on the play's genesis and reception, focussing specifically on the impact of her continued association with the role of Paula in Arthur Wing Pinero's The Second Mrs Tanqueray, her landmark performance of 1893. Reading Paula and Eliza against each other – and through the body of Stella Campbell – I consider these characters as hybrid figures, a reading that in turn highlights Campbell's own hybrid status and her consequent displacement in the British theatrical establishment of the early twentieth century.